Pediatric Neuropsychology Case Studies From the Exceptional to the Commonplace - Apps, Jennifer Niskala; Newby, Robert F.; Roberts, Laura Weiss; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Pediatric Neuropsychology Case Studies: From the Exceptional to the Commonplace. Edited by Jennifer Niskala Apps, Robert F. Newby, and Laura Weiss Roberts, Medical College of Wisconsin, Milwaukee Pediatric Neuropsychology Case Studies combines an evidence-based guide to frequently seen neurological and developmental disorders in children with compelling case histories, highlighting the uniqueness of every young client$1 (Band the skills involved in providing effective evaluation and treatment for every client$1 (Bto create an innovative, one-of-a-kind resource. The book$1 (Bs chapters, which can be read in sequence or in order of interest, offer typical and complex presentations of a broad range of developmental and acquired conditions including ADHD (combined, inattentive), traumatic brain injury (with age- and region-specific cases), psychiatric disorders, pervasive developmental disorders, systemic infections, reading and nonverbal disabilities, sensory and auditory problems, seizure disorders, and genetic disorders. Readers will appreciate the balance of coverage, whether it$1 (Bs between mainstream and alternative treatments or neurological and psychosocial aspects of a case. A chapter that highlights the interaction between neuropsychological assessment and on-going therapeutic interventions is also included. Helpful features in this practitioner-friendly volume are designed to enhance the reader$1 (Bs clinical comprehension, analytical thinking, and decision-making skills: Glossaries explain terminology essential to the cases. Common differential diagnosis issues are discussed. Relevant research findings and test data are reviewed for each chapter. Treatment recommendations are featured from best practice and emerging areas of study. Charts, tables, and callout boxes emphasize critical information. With intriguing chapters like "On Eggshells" and "Beating the Odds," Pediatric Neuropsychology Case Studies is instructive and challenging reading for novice and seasoned professionals in neuropsychology and neuropsychiatry, child psychologists and psychiatrists, school and counseling psychologists, and rehabilitation specialists.s
Dangers of Childhood: Neurological Disorders -- Beating the Odds: Prematurity and Posthemorrhagic Hydrocephalus -- Never, Ever Shake a Baby: Pass It On -- Grand Larceny in the First Grade: Traumatic Brain Injury in the School-Aged Years -- A Slippery Descent: Adolescent Traumatic Brain Injury -- Steamrolled: Sports-Related Concussions -- Bad Signs: Sickle-Cell Disease and Stroke -- Life Interrupted: Medulloblastoma -- The Mystery of the Falling Grades: Seizure Disorder -- When Half a Brain is Better than One: Recurrent Seizures -- Pathological Left-Handedness: Stroke and Seizures -- Moving Forward: Psychotherapy with a Youth After Brain Injury -- Family Matters: Psychosocial Factors on Neuropsychological Outcome -- Dog Attack: Physical Trauma with Associated Brain Injury -- Back to Life: Anoxic Brain Damage in a Near Drowning -- How It Can All Go Wrong: Developmental Disorders -- The Energizer Bunny Meets Shirley Temple: Attention Deficit Hyperactivity Disorder, Combined Type -- (3z(BHe is not Working up to Potential(3y(B: Atypical Attention Deficit Hyperactivity Disorder with Executive Weaknesses -- Sorting Sounds: Reading Disability with Phonological Awareness Deficit -- Well Compensated But Never Quite Solved: Lingering Dyslexia -- Emily Confronts Her Fiercest Bear: Word Reading Disorder with Naming Speed and Phonological Deficits -- A Tale of Two Assessments: Reading Fluency -- Lost in Space: Nonverbal Learning Disability -- Beyond Diagnosis: Applied Behavior Analysis Treatment of Moderate Autism Spectrum Disorder -- When Quirks and Quick Learning Create a Quandary: Mild Autism -- On Eggshells: Pediatric Bipolar Disorder -- It Helps to Know Genetic Basis: Williams Syndrome as an Example of Cognitive Disability -- Mixed Bag: Tics, Compulsions, and More -- Things that Go Bump in the Night: Interesting Questions and Controversies for Our Field -- A (3z(BSensational(3y (BWay to Understand and Serve Children: Illustration of a Sensory Processing Model -- Sense and Sensibility: Relating Behavior Control Issues with Self-Regulation of Sensory Input -- Elusive, Inclusive, or Conclusive? (Central) Auditory Processing Disorder -- A Little of This, A Little of That: (Central) Auditory Processing Disorder -- A Hunt for the Elusive Neuropsychological Impairment: Conversion Disorder -- A Mystery of Perplexing Symptoms: Neuropsychological Assessment in a Case of Dysautonomia -- Erratum.s
Keywords: Philosophy (General).; Neurology; Psychiatry; Psychology, clinical; Developmental psychology; Psychology; Neuropsychology; Psychiatry; Neurology; Clinical Psychology; Child and School Psychology